MODEL PENETAPAN HARGA IPO BERDASARKAN VALUATION - Aty Herawati; Noer Azam Achsani; Sri Hartoyo; Roy Sembel (MIX: JURNAL ILMIAH MANAJEMEN, 2016)
Abstract : The process of initial public offering of a company to the investors calledIPO (Initial Public Offering). .At time the company do an IPO, the shares price at IPOwas an agreement between the company and its underwriter. The phenomenon thatoccurs is the shares price at IPO lower than the intrinsic shares price based onvaluation, after the shares has been traded on the stock exchange, the phenomenon thatoccurs is IPO share price lower than the closing price on the first day. The purpose ofthis research is to create a model of how to set the share price at the time the companywill conduct IPO based on intrinsic share price valuation results. The valuation methodused is the Price to Earning Ratio. Research carried out on companies that did an IPOin 2000 - 2014 with a purposive sampling of 240 companies. The results showed therewas a difference between intrinsic shares prices based on the valuation and the sharesprice that set at the time of IPO. After the shares listed in the secondary market, therewas a difference between IPO share price and the closing price on the first day.Meanwhile, there is no difference between the intrinsic shares price and the closingprice on the first day, so in order to avoid underpricing, the IPO price can be predictedbased on intrinsic shares price valuation.